Genetic analysis and quality assessment of durum wheat (Triticum turgidum L.) landraces in Ethiopia - Mulatu Aberra Ebsa; Bulti Tesso; Tesfaye Letta (Cogent Food & Agriculture, 2024)
Ethiopia is rich in durum wheat diversity; however, national average productivity of durum wheat is low due to lack of strong national research program, and these calls for development of improved new varieties. Knowledge on extent of genetic variability and identification of important characters are a prerequisite for the development yielder and quality variety. Therefore, the present study was carried out to assess the extent of genetic variability and character association among yield and yield related traits in selected Ethiopian durum wheat landraces. Forty nine durum wheat accessions were studied for 20 traits at Sinana and Selka locations by using 7 × 7 simple lattice design in 2018/19. Combined analysis of variance revealed significant differences among accessions for all traits, indicating the presence of considerable variability among genotypes. A significant accession by locations interaction effect was observed which indicates differential performance of genotypes over environments. Protein content varied from 10.7%–16.7% with the overall mean of 13.5%. Also phenotypic coefficients of variation (PCV) ranged from 2.93 for hectoliter weight (HLW) to 27.08 for productive tillers (PTL) while, genotypic coefficients of variation (GCV) ranged from 0 for wet gluten (WGL) to 16.43 for vitreous (VTR). Low to high heritability was observed for the studied traits. Similarly, genetic advance as percent of mean varied from −0.20–31.24. High broad sense heritability and high genetic advance were obtained for grain yield (GY) (86.57 and 31.24) and vitreous (VTR) (75.76 and 29.39), respectively, indicating traits could be improved easily through selection. Overall, the present study revealed that there is sufficient variability existed in Ethiopian durum wheat landraces.